Chemical and biocidal investigations on rhizome volatile of curcuma zedoaria rosc-part 32 - Singh, Gurdip (2003)
Chemical investigation on Curcuma zedoaria rhizomes volatile oil, using HPLC, GC and GC/MS techniques, showed the presence of 1,8-cineole (18.5%), o- and p-cymene (18.42%) and alpha-phellandrene (14.93%) as major constituents followed by terpinolene (4.11%), alpha-pinene (3.28%), beta-turmerone (3.1%), beta-pinene (2.93%), beta-phellandrene (2.0%), etc. This oil was found in the highly insecticidal against Odontotermes obesus Rhamb. (white termite) and the minimum dose for 100% mortality was recorded as 2 uL per petriplate for 24 h exposure duration. It also showed complete mycelial inhibition of Colletotrichum falcatum at 4 uL per petriplate of the oil and was ineffective in controlling the mycelial growth of Aspergillus terrus, Fusarium graminearum, F. solani and Curvularia pallescens.